Influence of alumina/MWCNT hybrid nanoparticle additives on tribological properties of lubricants in turning operations - Anuj Kumar Sharma; Jitendra Kumar Katiyar; Shubrajit Bhaumik; Sandipan Roy (Friction)
Abstract A hybrid lubricant with improved thermal and tribological properties was developed by blending multiwalled carbon nanotubes (MWCNTs) with alumina-based nanoparticles into cutting fluid at fixed volumetric proportions (10:90). The hybrid cutting fluid was prepared in different volumetric concentrations (0.25, 0.75, and 1.25 vol%), and the tribological properties and contact angles were measured using pin-on-disc tribometry and goniometry, respectively. The study showed a reduction in wear and friction coefficient with increasing nanoparticle concentration. The cutting fluid performance was investigated using minimum quantity lubrication (MQL) in the turning of AISI 304 stainless steel. Regression models were developed for measuring the temperature and tool flank wear in terms of cutting speed, feed, depth of the cut, and nanoparticle concentration using response surface methodology. The developed hybrid nanolubricants significantly reduced the tool flank wear and nodal temperature by 11% and 27.36%, respectively, as compared to alumina-based lubricants.